Tinjauan Yuridis Kewenangan Komisi Pemberantasan Korupsi Dalam Monitoring Pemberantasan Tindak Pidana Korupsi Di Indonesia - Ferris Sustiawan; Erdianto Efendi; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Combating Corruption Commission (KPK) is a special institution established as an institution for combating corruption is formed by Act No. 30 of 2002 on the Corruption Eradication Commission. The Commission has the authority that an arbitrary one of the main organizers is to monitor the state government. Monitoring is an activity that is carried out to check the appearance of the activity that is being done. Sector Monitoring Commission, in charge of running the oversight of government agencies, especially that could affect the growth or shrinkage of the corruption perception index. commission work together with the Commission's internal watchdog agency to talk about how to create an effective supervision. Internal watchdog agency is spearheading the supervision of an institution or department. They are expected to be able to detect irregularities in advance or even prevent the occurrence of financial irregularities.Keywords: Authority - Monitoring - Combating Corruption Commission (KPK).